Firm-level prices, quality, and markups: The role of immigrant workers - Giulia Sabbadini (Review of International Economics, 2024)
In this article, I study export quality as a channel through which immigrant workers affect the export prices and markups of French manufacturing firms. I find that the share of immigrant workers in a local labor market is positively associated with firm-level export prices and quality and that this quality advantage translates to higher markups. I present evidence for the mechanism accounting for these relationships and find that the presence of immigrant workers is positively associated with firms importing higher-price (higher-quality) intermediate inputs, which are key to producing higher-price (higher-quality) exports. The hypothesized economic mechanism is that immigrant workers help firms overcome informational barriers to sourcing higher-price (higher-quality) inputs from abroad. I provide evidence consistent with immigrant workers having specialized knowledge of the upstream market.
Keywords: 330; exports; immigrant workers; intermediate inputs; markups; prices; quality